2018
DOI: 10.21037/jtd.2018.02.63
|View full text |Cite
|
Sign up to set email alerts
|

Antiplatelet and anticoagulant for prevention of reocclusion in patients with atrial fibrillation undergoing endovascular treatment for low extremity ischemia

Abstract: The mono antiplatelet plus anticoagulation therapy offers a safe and effective alternative for prevention of reocclusion in patients with AF undergoing endovascular treatment for lower extremity ischemic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…The following advantages of rivaroxaban should be noted: no temporary hypercoagulable state, stable anticoagulation effect, fewer drug–food or drug–drug interactions, and less unnecessary INR monitoring to adjust the dose ( 8 , 16 , 17 ). Previous studies have indicated that rivaroxaban affects protease-activated receptors to inhibit cell signalling in atrial myocytes or endothelial cells, thus playing an important role in the pro-inflammatory response to prevent related adverse events ( 8 , 18 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The following advantages of rivaroxaban should be noted: no temporary hypercoagulable state, stable anticoagulation effect, fewer drug–food or drug–drug interactions, and less unnecessary INR monitoring to adjust the dose ( 8 , 16 , 17 ). Previous studies have indicated that rivaroxaban affects protease-activated receptors to inhibit cell signalling in atrial myocytes or endothelial cells, thus playing an important role in the pro-inflammatory response to prevent related adverse events ( 8 , 18 ).…”
Section: Discussionmentioning
confidence: 99%
“…In our research, the dose of rivaroxaban administered to the patients was 10 mg per day, and the dose reduction was mainly attributed to the following: (i) The median age of the patients in our cohort was 80.0 years (range, 71.0–84.0 years), which is higher than those in AF registry trials (e.g., 73 years in the ROCKET-AF trial; 71.5 years in the XANTUS trial). (ii) For these patients, renal creatinine clearance probably declines, and the time for rivaroxaban to be metabolised in the body will be prolonged ( 18 , 20 , 21 ). (iii) More importantly, a considerable number of patients in our cohort required single -antiplatelet or dual APT regimens postoperatively.…”
Section: Discussionmentioning
confidence: 99%
“…Postoperative anticoagulation was performed accordingly. 9,10,15 The patients with arterial embolism that was resulted from atrial fibrillation, coronary heart disease, rheumatic heart disease, and thoracoabdominal aortic aneurysm, received the following postoperative anticoagulation therapy: low molecular heparin (100 u/kg of injection) after the procedure and oral administration of Warfarin (INR: 2–3) or Rivaroxaban (20 mg per day) after discharge from hospital. The patients with cardiogenic emboli were maintained on long-term anticoagulation with warfarin sodium.…”
Section: Methodsmentioning
confidence: 99%